Race, crime, and the micro-ecology of deadly force - Klinger, David (Criminology & public policy, 2016)
Limitations in data and research on the use of firearms by police officers in the United States preclude sound understanding of the determinants of deadly force in police work. The current study addresses these limitations with detailed case attributes and a microspatial analysis of police shootings in St. Louis, MO, between 2003 and 2012. The results indicate that neither the racial composition of neighborhoods nor their level of economic disadvantage directly increase the frequency of police shootings, whereas levels of violent crime do—but only to a point. Police shootings are less frequent in areas with the highest levels of criminal violence than in those with midlevels of violence. We offer a provisional interpretation of these results and call for replications in other settings.